2018
DOI: 10.1038/s41390-018-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastric fluid used to assess changes during the latency period in preterm prelabor rupture of membranes

Abstract: The microbial and inflammatory status of the intraamniotic compartment changes during the latency period in PPROM. Bedside IL-6 assessment of gastric fluid may be useful in the rapid diagnosis of funisitis and FIRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…We have found that the earlier the gestational week of the PPROM is, the longer the latency period is, which is consistent with the results of previous reports [21,22] , and the pregnant women whose membrane rupture occurs before 32 weeks have a greater probability of latency period > 168h. It's been reported [23] that expecting a time longer than 1 week does not increase the risk of HCA, so pregnant women who have ruptured membranes before 32 weeks should keep the latency period more than one week.…”
Section: Discussionsupporting
confidence: 92%
“…We have found that the earlier the gestational week of the PPROM is, the longer the latency period is, which is consistent with the results of previous reports [21,22] , and the pregnant women whose membrane rupture occurs before 32 weeks have a greater probability of latency period > 168h. It's been reported [23] that expecting a time longer than 1 week does not increase the risk of HCA, so pregnant women who have ruptured membranes before 32 weeks should keep the latency period more than one week.…”
Section: Discussionsupporting
confidence: 92%
“…Preterm prelabor rupture of membranes (PROM) is widely used as an inclusion criterion for predictions of other conditions. [1][2][3][4][5][6][7][8] The disease precedes 40%~50% of all preterm deliveries and arises from multiple disease pathways. 9 Yet, the antecedent remains unclear, and prognostic predictions lack proper sample sizes and external validation.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the rat animal model of intra-amniotic inflammation was not associated with the risk of labor induction within 24 h is important from a research standpoint because it provides an opportunity to collect various body fluids and tissues from gestational sacs after their exposure to intra-amniotic inflammation. This approach mimics human clinical scenarios ( Musilova et al, 2018 ; Kacerovsky et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%